2‐Acetyloxymethyl‐substituted 5, 6, 7‐trihydroquinolinyl‐8‐ylideneamine‐Ni(II) chlorides and their application in ethylene dimerization/trimerization. (21st October 2019) - Li, Jiaxin; Zhang, Qiuyue; Hu, Xinquan; Ma, Yanping; Solan, Gregory A.; Sun, Yang; Sun, Wen‐Hua
Abstract: Six examples of 2‐acetyloxymethyl‐substituted 5, 6, 7‐trihydroquinolinyl‐8‐ylideneamine‐nickel(II) chlorides, [2‐(CH2 OC(O)Me)‐8‐N(Ar)C9 H8 N]NiCl2 (Ar = 2, 6‐Me2 C6 H3 Ni1, 2, 6‐Et2 C6 H3 Ni2, 2, 6‐i‐Pr2 C6 H3 Ni3, 2, 4, 6‐Me3 C6 H2 Ni4, 2, 6‐Et2 –4‐MeC6 H2 Ni5, 2, 4, 6‐t‐Bu3 C6 H2 Ni6 ), have been prepared by a one‐pot template reaction of 2‐(hydroxymethyl)‐6, 7‐dihydroquinolin‐8(5H)‐one with nickel dichloride hexahydrate, the corresponding aniline and acetic acid. All complexes were characterized by elemental analysis and IR spectroscopy, while dinuclear Ni2 and mononuclear Ni3 ·OH2 have additionally been the subject of single crystal X‐ray diffraction studies; in both structures the acetyloxymethyl group remained uncoordinated. On activationof Ni1 – Ni6 with MMAO, hexenes (C6: ca. 48% 1‐hexene) formed the major product of ethylene oligomerization along with minor quantities of butenes (C4); high overall activities of up to 1.33 × 10 6 g·mol–1 (Ni)h–1 (for mesityl‐containing Ni4 ) were achieved at 30 o Cand 10 atm C2 H4 . By comparison with MAO as co‐catalyst, Ni1 – Ni6 exhibited lower activities but displayed a specificity towards ethylene dimerization (C4: 64–99% 1‐butene). Furthermore, sizable induction periods were a feature of the MAO runs with Ni1 /MAO reaching peak catalytic activity only after 45 mins. Abstract : The title 2‐acetyloxymethyl‐substituted N, N ‐nickel dichlorides show distinct selectivities for ethylene dimerization and trimerization that are dependent on the type of aluminoxane used to activate them.